Physician assessments of drug seeking behavior: A mixed methods study. - Michael A Fischer; John B McKinlay; Jeffrey N Katz; Eric Gerstenberger; Felicia Trachtenberg; Lisa D Marceau; Lisa C Welch (PLoS ONE, 2017)
Background Pain complaints are common, but clinicians are increasingly concerned about overuse of opioid pain medications. This may lead patients with actual pain to be stigmatized as "drug-seeking," or attempting to obtain medications they do not require medically. We assessed whether patient requests for specific opioid pain medication would lead physicians to classify them as drug-seeking and change management decisions. Methods and findings Mixed-methods analysis of interviews with 192 office-based primary care physicians after viewing video vignettes depicting patients presenting with back pain. For each presentation physicians were randomly assigned to see either an active request for a specific medication or a more general request for help with pain. The main outcome was assignment by the physician of "drug-seeking" as a potential diagnosis among patients presenting with back pain. Additional outcomes included other actions the physician would take and whether the physician would prescribe the medication requested. A potential diagnosis of drug-seeking behavior was included by 21% of physicians seeing a specific request for oxycodone vs. 3% for a general request for help with back pain(p<0.001). In multivariable models an active request was most strongly associated with a physician-assigned diagnosis of drug-seeking behavior(OR 8.10; 95% CI 2.11-31.15;p = 0.002); other major patient and physician characteristics, including gender and race, did not have strong associations with drug-seeking diagnosis. Physicians described short courses of opioid medications as a strategy for managing patients with pain while avoiding opioid overuse. Conclusions When patients make a specific request for opioid pain medication, physicians are far more likely to suspect that they are drug-seeking. Physician suspicion of drug-seeking behavior did not vary by patient characteristics, including gender and race. The strategies used to assess patients further varied widely. These findings indicate a need for the development of better clinical tools to support the evaluation and management of patients presenting with pain.